(3bhGfjf GdGbJUGO GdGSdGej aj GdeLJeYGJ GdYQHjI h GdGSdGejI (B/s - (3YjO , YGOd YHO GdaVjds ((3GdGScfOQjI (B: s (3OGQ GdacQ GdLGeYj(B, s, 2009)
)(3bhGfjf GdeUGQa GdGSdGejI (B: (3fXGe eQGbHI GdHfhc GdSYhOj , Hfc fGUQ GdGLJeGYj , GdHfc GdGSdGej ddJfejI , Hfc OHj GdGSdGej , Hfc ajUd GdGSdGej GdeUQj , Hfc ajUd GdGSdGej GdShOGfj , Hfc GdJehjd GdchjJj , GdHfhc , GdHfhc GdGSdGejI aj GdGQOf , GdeUGQa h GdeDSSGJ GdeGdjI h GdTQcGJ GdGSJKeGQjI GdGSdGejI GdbGfhf GdGJMGOj GdGeQGJj , bGfhf HjY GdGehGd GdeQghfI ddeUGQa aj GdShOGf , GdeUGQa GdGSdGejI aj Gdjef,GdeUGQa GdadSWjfjI , JfXje GdYed GdeUQaj aj GdShOGf , Hfc GdShOGf GdeQcRj , GdeUGQa GdGSdGejI aj ShQjG (B2)(3GdYbhO GdGbJUGOjI (B: (3JMQje QHG GdfSjFI aj GdeYGedGJ GddjHjI , fXGe GdHjY HGdJbSjW aj GdSYhOjI , GdHjY HGdJbSjW aj GdchjJ , GbJQGM eTQhY bGfhf GdHjY HGdJbSjW , JMQje GbJUGO GdeVGQHI aj djHjG (B03) (3GdRcGI (B: (3bGfhf GdRcGI h GdYTQ aj LeghQjI GdHGcSJGf GdGSdGejI , bGfhf EfTGA HjJ GdRcGI GdchjJj , bGfhf UfOhb GdRcGI aj GdGQOf h UfOhb GdRcGI aj bWQ , bhGfjf GdRcGI aj GdSYhOjI h aj Gdjef h aj GdShOGf h eTQhY bGfhf GdRcGI aj eUQ , bGfhf GdRcGI ddgjFI GdYGdejI ddRcGI (B04)(3Gdhba (B: (3bGfhf CMcGe Gdhba aj eUQ , fXGe eLdS GdGhbGa GdGYdi aj GdSYhOjI , bGfhf GdGhbGa GdNjQjI aj GdShOGf h aj GdLRGFQ h aj bWQ h GdGQOf , eTQhY bGfhf CMcGe Gdhba (B05) (3GdhUGjG h GdehGQjK(B: (3bGfhf GdehGQjK h bGfhf GdhUjI aj eUQ , GdhUGjG h GdehGQjK aj bGfhf GdGMhGd GdTNUjI HShQjI h HGdchjJ , bGfhf GdhUjI GdhGLHI GdchjJj , GdhUGjG h GdehGQjK aj bGfhf GdGMhGd GdTNUjI aj GdGQOf h aj bWQ h aj GdGeGQGJ GdYQHjI GdeJMOI (B.s
(3eQGLY U(B.731s
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdGSdGejs